Surgical management of facial dog bite trauma: A contemporary perspective and review - Tiffany Chen; Maria Karim; Zachary T. Grace; Andrew R. Magdich; Eric C. Carniol; Brian E. Benson; Peter F. Svider (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2023)
Abstract Objective To perform a review evaluating management of and complications stemming from dog bite trauma sustained to the head and neck over the past decade. Data Sources PubMed and Cochrane Library. Methods The authors searched the PubMed and Cochrane Library databases for relevant published literature. A total of 12 peer‐reviewed canine‐exclusive series inclusive of 1384 patient cases describing facial dog bite trauma met inclusion criteria. Wounds including fractures, lacerations, contusions, and other soft‐tissue injuries were evaluated. Demographics related to clinical course and management, operating room requirements, and antibiotic usage were compiled and analyzed. Initial trauma and surgical management complications were also assessed. Results 75.5% of patients sustaining dog bites required surgical intervention. Of these patients, 7.8% suffered from postsurgical complications, including hypertrophic scarring (4.3%), postoperative infection (0.8%), or nerve deficits and persistent paresthesias (0.8%). Prophylactic antibiotics were administered to 44.3% of patients treated for facial dog bites and the overall infection rate was 5.6%. Concomitant fracture was present in 1.0% of patients. Conclusion Primary closure, often in the OR may be necessary, with few cases requiring grafts or flaps. Surgeons should be aware that the most common complication is hypertrophic scarring. Further research is needed to elucidate the role of prophylactic antibiotics.